Prevalence, awareness, treatment and control of hypertension and sodium intake in Jiangsu Province, China: a baseline study in 2014. (December 2015) - Yongqing, Zhang; Ming, Wu; Jian, Su; Pengfei, Luo; Xiaoqun, Pan; Meihua, Dong; Peian, Lou; Jianmei, Dong; Guoyu, Zhou; Jie, Yang; Ping, Lin; Yan, Xu
Abstract Background The prevalence of hypertension in Chinese Mainland has increased rapidly in the recent decades. This study aimed to determine the prevalence of hypertension and sodium intake in an economically booming area in China. Methods 9600 adults aged from 18 to 69 years old in Jiangsu Province of China were recruited using a complex, multistage sampling method. Blood pressure was measured and a face-to-face interview was conducted among all participants. 24 hours (24-h) urine sample was collected from each participant and then measured for sodium and potassium. Hypertension was determined by blood pressure and use of anti-hypertension medications. All of the analyses were weighted according to the population distribution in the province. Results Overall, the weighted means of systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 128.8 mm Hg (95 % confidence interval, CI, 128.3–129.3) and 82.2 mm Hg (95 % CI, 81.4–83.1). The weighted hypertension prevalence of Jiangsu residents was 33.0 % (95 % CI, 29.4–36.7 %). Among those with hypertension, 31.4 % (95 % CI, 24.6–38.1) were aware of their blood pressure condition. In total, 88.4 % (95 % CI, 83.5–93.3) of those with known hypertension took anti-hypertension medications. Only 23.7 % (95 % CI, 13.3–34.2) of those under anti-hypertension medications had their blood pressure controlled. The mean of 24-h urinary sodium excretion was 188.2 mmol (standard deviation, SD, 69.5), representing that the mean intake of salt was 11.0 g (SD, 4.1) through conversion. Conclusion Hypertension and excessive sodium intake in adults are prevalent in Jiangsu Province, China. These observations suggest that a public health approach is necessary to prevent hypertension and manage hypertensive patients.